Clinical assessment of reactive balance control in acquired brain injury: A comparison of manual and cable release‐from‐lean assessment methods. (17th June 2019) - Borrelli, James R.; Junod, Christiane A.; Inness, Elizabeth L.; Jones, Simon; Mansfield, Avril; Maki, Brian E.
Abstract: Objective: Perturbation‐evoked stepping reactions are infrequently assessed directly in clinical settings even though stepping reactions in response to a sudden loss‐of‐balance perturbation ultimately determine whether a fall occurs. Individuals with acquired brain injury (ABI) due to stroke who are ambulatory and awaiting hospital discharge have been found to exhibit delayed stepping reactions but are typically discharged without assessment of perturbation‐evoked stepping. Tests that specifically target the capacity to perform perturbation‐evoked stepping reactions are important to identify those at risk for falls and to direct intervention strategies. The aim of this study was to evaluate agreement and reliability of two assessment methods used to assess rapid stepping reactions, specifically in individuals with ABI due to stroke or other causes. A secondary aim was to compare perturbation‐triggered biomechanics of the two assessment methods. Methods: Thirty‐five participants who were less than 4 months post‐ABI were evaluated in an inpatient unit at the Toronto Rehabilitation Institute. Stepping reactions were assessed using manual release‐from‐lean and cable release‐from‐lean perturbation‐based assessment methods. Results: There was moderate agreement between the assessment scores resulting from the two assessment methods ( κ  = 0.55) and substantial test–retest reliability ( κ 's > 0.61) for both assessment methods. There was no evidence that the assessment score was affected by assessment method, test–retest, or assessment order. However, the cable release from lean resulted in a more rapid release of the lean support force (2 ms vs. 125 ms) and earlier foot‐off times (340 ms vs. 401 ms) compared with the manual release from lean. Conclusion: Delays in foot‐off time associated with the manual release‐from‐lean perturbation raise concerns that the manual assessment method may not provide a perturbation that is sufficiently challenging to reveal a patient's balance‐recovery capacity and associated fall risk. However, the manual assessment requires no equipment and the assessment score may provide a useful indication of gross reactive balance control.